Penerapan Model Pembelajaran Cooperative Learning Tipe Jigsaw untuk Meningkatkan Hasil Belajar Siswa pada Materi Rukun Islam di Kelas IV SD Negeri 034 Pintu Padang Julu - Sujuan Rido; Nurhidayah; Zulkifli; Devi Solita; Derina Hasibuan (CV. Alfa Pustaka, 2025)
This classroom action research aimed to improve student learning outcomes in Islamic Pillars material through the implementation of Cooperative Learning model with Jigsaw technique in fourth grade of SD Negeri 034 Pintu Padang Julu. The study involved 28 students and was conducted in two cycles using the Kemmis and McTaggart model. Data collection techniques included observation, tests, and documentation. The results showed significant improvement in student learning outcomes from pre-cycle with only 32.14% students achieving minimum criteria to 57.14% in cycle I and 89.29% in cycle II. Student activity also increased from 64.29% in cycle I to 85.71% in cycle II. The Jigsaw model effectively enhanced student collaboration, responsibility, and understanding of Islamic Pillars material. Students became more active in discussions, confident in presenting, and demonstrated better comprehension of each pillar's meaning and implementation. This research concluded that Cooperative Learning with Jigsaw technique is effective for improving learning outcomes in Islamic education.